PROSES PENCIPTAAN Aâ€™BIRING BONE DI KAMPUNG KUNYIâ€™ DESA BAHOREA KECAMATAN BONTOSIKUYU KABUPATEN KEPULAUAN SELAYAR SULAWESI SELATAN Bau Salawati - Bau Salawati (Greget, 2014)
Aâ€™biring Bone is the name of a dance work which is performed in Kampong Kunyiâ€™ in the Village ofBahoreain the Sub-District of Bontosikuyuin the Kepulauan Selayar District of the South Sulawesi Province.The way in which the Aâ€™biring Bone dance â€“ whichin the Selayar language means â€œscouring the coastlineâ€ â€“isconstructed is closely connected to the local community, as it involves the people who live along the coast ofKampong Kunyiâ€™. Aâ€™biring Bone is a work which tells about the lives of the people in the fishing communitywho move from Kampong Tile-Tile to Kampong Kunyiâ€™ when the west monsoon season arrives, and hold aritual before going out to sea and a communal celebration to give thanks for an abundant harvest. This workalso presents a traditional dance that is found in the Sub-District of Bontosikuyu in the KepulauanSelayarDistrict of the South Sulawesi Province, namely the Pakarena BallaBulo dance.Keywords: Form, Creation, Aâ€™biring Bone